Pengaruh Elektabilitas Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Tingginya Turnover Karyawan PT. Sumi Rubber Indonesia - Ridwansyah, Ridwansyah; Purwadhi, Purwadhi; Andriani, Rian (LPPM Universitas Buana Perjuangan Karawang, 2023)
The purpose of this research was to find out and analyze the influence of the electability of leadership style and work environment on employee turnover at PT. Sumi Rubber Indonesia together. This research uses a quantitative approach. The samples in this study were employees at PT. Sumi Rubber Indonesia with a total of 73 people. Data collection in this study was in the form of a questionnaire. The data analysis techniques are validity test, reliability test, classical assumption test and multiple linear regression analysis. Hypothesis testing using, t test, f test, R test and R2 test. The results showed that: 1) The electability of leadership style has a significant effect on employee turnover, 2) The work environment has a significant effect on employee turnover, 3) The electability of leadership style and work environment has a significant effect on employee turnover in the Directorate of Sales and Marketing Keywords: Electability of Leadership Style, Work Environment and Employee Turnover